Comparison of osmotic dehydration and ultrasound-assisted osmotic dehydration on the state of water, texture, and nutrition of Agaricus bisporus - Pei Fei; Chen Lifu; Yang Wenjian; Zhao Liyan; Fang Yong; Ma Ning; Hu Qiuhui (CyTA - Journal of Food, 2018)
To improve product quality and osmotic efficiency, the effects of osmotic dehydration (OD) at 120 min and ultrasound-assisted osmotic dehydration (UOD) at 45 min on the nutrient composition, flavor, texture, microstructure, and water state in button mushrooms were investigated. In terms of nutrient composition, the results showed that UOD produced samples with reducing sugar, ascorbic acid, and soluble protein content at significantly higher rates than OD process. Meanwhile, UOD reduced the losses in titratable acidity, free amino acids, and 5′-nucleotides compared to the OD process, and the UOD samples also showed a better texture and microstructure. In addition, low-field nuclear magnetic resonance data revealed that the relative signal intensity of vacuole protons declined during OD process; meanwhile, the UOD was more efficient than the OD treatment. Overall, UOD process not only retained nutrient composition and flavor material more effectively but also improved the texture and efficiency of mushrooms treated with osmosis.